2019
DOI: 10.1161/atvbaha.118.312215
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Deficiency Protects Against Atherosclerosis

Abstract: Objective— Inflammatory stimuli enhance the progression of atherosclerotic disease. Inflammation also increases the expression of hepcidin, a hormonal regulator of iron homeostasis, which decreases intestinal iron absorption, reduces serum iron levels and traps iron within macrophages. The role of macrophage iron in the development of atherosclerosis remains incompletely understood. The objective of this study was to investigate the effects of hepcidin deficiency and decreased macrophage iron on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…Conversely, in another study deletion of the hepcidin gene ( hamp ) was associated with reduced atherosclerosis in hamp −/− /Ldlr −/− mice along with reduced pro-inflammatory markers in macrophages [73]. In addition, fasting serum LDL was decreased, which might in part be attributable to a genetic overlap in iron and lipid loci [47].…”
Section: Opportunities and Future Directions: Modulation Of Iron Metamentioning
confidence: 99%
“…Conversely, in another study deletion of the hepcidin gene ( hamp ) was associated with reduced atherosclerosis in hamp −/− /Ldlr −/− mice along with reduced pro-inflammatory markers in macrophages [73]. In addition, fasting serum LDL was decreased, which might in part be attributable to a genetic overlap in iron and lipid loci [47].…”
Section: Opportunities and Future Directions: Modulation Of Iron Metamentioning
confidence: 99%
“…wild-type, Mgp −/− Hdac9 +/+ , Mgp −/− Hdac9 +/− , and Mgp −/− Hdac9 −/− mice were injected via the tail vein with OsteoSense-680 (PerkinElmer, 5 μl/g each) 24 hours before euthanasia, as described previously 50,51 . Aortas were isolated and analyzed ex vivo by fluorescence reflectance imaging using an Odyssey Imaging System (LI-COR Biotechnology, Lincoln, NE) and software version 3.0.16 52,53 .…”
Section: Near-infrared Imaging and Quantification Of Aortic Calcificamentioning
confidence: 99%
“…In addition to the characterized linking function of adropin 19 and fetuin 33 , a recent study reported that alpha-1-microglobulin (AMBP) exacerbated inflammation and disturbed hepatic fibrotic repair after myocardial infarction through activating Akt, NF-κB, and ERK signaling and promoting macrophage migration and polarization 115 . Another hepatokine, hepcidin, has been proven to regulate macrophage inflammation and arterial stiffness, thus promoting the development of atherosclerosis 116 , 117 . Upregulated fetuin B aggravates myocardial ischemia/reperfusion injury through inhibiting insulin signaling in diabetic mice 118 .…”
Section: Communications Between the Liver And Other Major Organsmentioning
confidence: 99%